2009
DOI: 10.1111/j.1365-4632.2008.03924.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes treated with peptidoglycan from Staphylococcus aureus produce vascular endothelial growth factor, and its expression is amplified by the subsequent production of interleukin‐13

Abstract: These results suggest that PGN from S. aureus can induce LL37 and VEGF expression in keratinocytes, and that this VEGF production can be amplified by subsequent IL-13 overproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…Despite evidence of an association with bacterial vaginosis, TLR agonists did not regulate LL-37 gene expression in cells derived from epithelia of the lower genital tract. This is in contrast to other studies which have shown that expression of CAMP is increased in response to TLR agonists, including POLY (I:C) and peptidoglycan, in other epithelial cell lines [18], [19]. This suggests different CAMP responses depending on cell type and environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite evidence of an association with bacterial vaginosis, TLR agonists did not regulate LL-37 gene expression in cells derived from epithelia of the lower genital tract. This is in contrast to other studies which have shown that expression of CAMP is increased in response to TLR agonists, including POLY (I:C) and peptidoglycan, in other epithelial cell lines [18], [19]. This suggests different CAMP responses depending on cell type and environment.…”
Section: Discussioncontrasting
confidence: 99%
“…Ruíz-González et al [27] also showed that keratinocytes treated with PGN increased IL13 production. Stimulation of IL13, a Th2 immune cytokine, led to an increase in crypt cell proliferation and goblet cell size and number via activation of PI3-kinase/AKT [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our strains were able to produce PG at concentrations ranging from 300 to 410 ng ml -1 . PG at a lower concentration of 2.5 μg ml -1 increased the expression of the LL37 in keratinocytes, leading to a protective effect in psoriatic skin lesions (RUIZ-GONZALEZ et al, 2009). Although a higher concentration of PG is required to stimulate the cellular immunity response and LL37 in keratinocytes, an induction response has been reported via synergism with LTA.…”
Section: Bioactivesmentioning
confidence: 97%